Cover Image, Volume 56, Issue 9. (2nd September 2021) - Zhao, Xiangdong; Wang, Wei; Xie, Guwei; Pan, Songqi; Jarzembowski, Edmund A.; Zheng, Daran
Abstract : The cover image is based on the Research Article Depositional environment of Middle Triassic organic‐rich shales in the Ordos Basin, Northwest China by Wei Wang et al., https://doi.org/10.1002/gj.4215 . Abstract : The cover image is based on the Research Article Depositional environment of Middle Triassic organic‐rich shales in the Ordos Basin, Northwest China by Wei Wang et al., https://doi.org/10.1002/gj.4215 .